2011
DOI: 10.1063/1.3561503
|View full text |Cite
|
Sign up to set email alerts
|

A photosensitive Cr3+ center in photorefractive Bi12SiO20 crystals co-doped with chromium and phosphorus

Abstract: ABSTRACT:A trigonal Cr 3+ (3d 3 ) defect in sillenite type Bi 12 SiO 20 crystals co-doped with chromium and phosphorus has been identified by means of multi-frequency X-band (9.4 GHz), Q-band (35 GHz) and W-band (94 GHz) electron paramagnetic resonance (EPR). A consistent analysis of the observed spectra and their angular dependence was reached using an S=3/2 spin Hamiltonian with axial symmetry around a <111> crystallographic direction, an isotropic g-value g = 1.983, and a zero field splitting parameter B 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Since electrical charges of both ions are not equal is needed a charge compensation, obtained by substitution of Bi 3+ ions with P 5+ ions [8].…”
Section: Figure1 Elementary Cell Of Bi 12 Sio 20 Crystalmentioning
confidence: 99%
See 2 more Smart Citations
“…Since electrical charges of both ions are not equal is needed a charge compensation, obtained by substitution of Bi 3+ ions with P 5+ ions [8].…”
Section: Figure1 Elementary Cell Of Bi 12 Sio 20 Crystalmentioning
confidence: 99%
“…Nevertheless, it should be pointed out that reports on the consistent crystal field analysis of Cr 3+ doped BSO crystals with calculations of crystal field parameters (CFPs) from structural data, and energy levels scheme, are scarce. The electron paramagnetic resonance (EPR) identifies a chromium ion in the unusual Cr 3+ valence replacing by substitution Si 4+ ions in tetrahedral oxygen coordination [8]. Evidence is found that the site symmetry of chromium ion is lowering from tetrahedral symmetry to trigonal one.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In literature, there are reports on the growth of Cr-doped BSO crystal and investigations on the photorefractive effect, dielectric property, optical activity, Faraday effect, etc. [15][16][17][18][19][20][21][22][23][24] For the growth of the crystal, Czochralski technique has been used as BSO is a congruently melting compound. [25,26] It is known that the devices mentioned earlier require crystals with a low dislocation density and high optical homogeneity.…”
mentioning
confidence: 99%
“…[7,8] It has been reported that the photorefractive property of BSO is enhanced significantly on doping with metals like Cr, Fe, Mg, Ru, etc. [8,[15][16][17][18][19][20][21][22][23][24][25][26][27] Though most of these dopants make material sensitive to photorefraction in the visible region, especially around 500 nm, that is, 2.5 eV, practical feasibility prefers the region near the infrared (1.5À2 eV), mainly because of the availability of compact laser diodes in this region. [28] Cr doping shifts the photorefractive sensitivity of BSO to the near-infrared region and therefore makes it a potential material for applications like optical image processing, holographic interferometry, optical storage, and phase conjugation.…”
mentioning
confidence: 99%